Effect of Infill Density and Infill Pattern on Mechanical Properties of 3D-printed PLA Produced by FFF - Akçay, Özlem; Arı, Ali (Fırat University, 2025)
With the rapid advancements in Additive Manufacturing (AM) technology, examining the mechanical properties of products utilized in this process has become increasingly important. The mechanical properties of 3D-printed products are significantly influenced by the choice of printing methods and printing parameters. Despite ongoing progress, research exploring these effects remains limited. Therefore, the aim of this study is to examine the effects of these production parameters on samples produced with PLA material with different infill densities and infill patterns using the fused filament fabrication technique, one of the AM methods. For this purpose, test samples with five patterns (cubic, tri-hexagon, octet, grid, and zigzag) and two densities (50%, 60%) were produced. In addition, 100% infill density was created with a solid infill pattern and selected as a reference. Mechanical tensile and Charpy tests were conducted on all samples. The results indicate that infill parameters have significant effects on the energy absorption and tensile strength of 3D-printed products. Printing patterns influence the tensile strength of printed structures, with octet-patterned structures showing the maximum tensile strength at 42 MPa and the highest energy absorption value at 16.94 kJ.mm-2. Furthermore, it was found that the tensile strength increases with increasing infill density. The values obtained from the mechanical tests in this study will serve as a reference for selecting the correct infill parameters in the slicing program for 3D-printed products requiring high-strength.

Eklemeli imalat (AM) teknolojisinin gelişmesiyle bu teknolojide kullanılan malzemelerin mekanik özellikleri üzerindeki etkilerini incelemek giderek daha önemli hale gelmektedir. Farklı baskı yöntemleri ve üretim parametrelerinin kullanılması, 3D-baskılı malzemelerin mekanik özelliklerini etkilemektedir. Ancak bu konuda araştırmalar hala sınırlıdır. Dolayısıyla, bu çalışmanın hedefi, AM metodu kullanılarak farklı dolgu yoğunluklarına ve dolgu desenlerine sahip PLA malzeme ile üretilen numuneler üzerinde bu dolgu işlem parametrelerinin etkilerini incelemektir. Bu amaçla beş dolgu desenine (cubic, tri-hexagon, octet, grid and zig zag) ve iki dolgu yoğunluğuna (50%, 60%) sahip test numuneleri üretilmiştir. Ek olarak %100 dolgu yoğunluğu, desensiz katı dolguya sahip olacak şekilde oluşturulmuş ve referans olarak seçilmiştir. Tüm numunelere mekanik çekme testi ve Charpy testi uygulanmıştır. Sonuçlar, doldurma parametrelerinin üç boyutlu olarak basılmış yapıların enerji emilimi ve çekme dayanımı üzerinde önemli etkileri olduğunu göstermektedir. Baskı desenleri, basılan yapıların çekme dayanımını etkiler, özellikle octet desenli yapıların, 42 MPa ile en iyi çekme dayanımı ve 16,94 kJ.mm-2 ile en yüksek enerji emilim değerine sahip olduğu tespit edilmiştir. Ayrıca dolgu yoğunluğunun artması ile çekme mukavemetinin de arttığı belirlenmiştir. Bu çalışmanın mekanik test sonucunda elde edilen değerleri, yüksek mukavemetli mekanik özelliklere ihtiyaç duyan 3B baskı ürünlerinde kullanılacak dilimleme uygulamasında doğru dolgu parametrelerini seçmede bir referans olacaktır.
FFF Kullanılarak Üretilen 3D Baskılı PLA’nın Mekanik Özellikleri Üzerinde Dolgu Yoğunluğu ve Dolgu Deseninin Etkisi
Keywords: Additive Manufacturing; Katmanlı Üretim